The Effects of Windthrow Damage on Soil Properties in Scots Pine, Black Pine and Kazdağı Fir Stands in the Northwest Turkey - Savaci, Gamze; Sarıyıldız, Temel; Caglar, Sadik; Kara, Ferhat; Topal, Esra (Kastamonu University, 2021)
Aim of study: The short-term effects of windthrow damage on soil properties were investigated in Kazdağı fir (Abies nordmanniana subsp. equi-trojani), Scots pine (Pinus sylvestris L.) and black pine (Pinus nigra Arnold.) stand in northwest Turkey. Area of study: The study was carried out in Kastamonu and Sinop regions. Material and methods: In order to understand the effects of windthrow damage occurred in 2013, soil samples were collected at a depth of 0-30 cm from the disturbed and undisturbed sites in 2018 (5 year later), and analyzed for soil physical and chemical properties. Main results: The increases in temperature, wind speed and heavy rainfall in the study sites seemed to result in the windthrows. There were significant differences in soil physical and chemical properties among the three tree species, and also between the disturbed and the undisturbed sites. Highlights: After the windthrows, increased SOC and TN stocks, P and K could be related to the accumulation of organic matter. However, we were not able to identify a single mechanism to explain this observed relationship. Thus, the root-soil interactions of the three tree species should be conclusively examined in future studies in order to define the relationships between soil chemical properties and root features.
Keywords: Tree Species; Soil Properties; Microclimate; Windthrow Damage; Carbon Stock; 2. Zero hunger; 15. Life on land